أكسيولوجيا الجمع بين الزمان والمكان في رسوم المنمنمات الإسلامية - Alasqha, شذى سامي (Basrah Arts Journal, 2025)
Islamic miniatures are creative works that are distinguished by their unique expressive formations across time, as they contain diverse intellectual, philosophical, cultural, social and religious connotations. They invite researchers to explore the hidden meanings of these connotations according to a scientific methodology to arrive at the axiology of artistic expression based on a scientific analysis of values, including the value of combining multiple times and different places in miniature. The objectives of the research were determined by clarifying the axiological concept in the arts to determine the axiology of combining time and place in Islamic miniatures. The research followed the historical, descriptive and analytical method, and the research sample consisted of four miniatures from Islamic manuscripts dating back to the sixteenth century AD. The research reached several results, the most important of which is that the Muslim artist expressed the axiology of combining time and place according to an integrated intellectual philosophy, and that the philosophy of aesthetic thought in Islamic arts contributed to shaping the axiological values ​​of integrating time and place in its arts.